2012
DOI: 10.1590/s0102-09352012000400009
|View full text |Cite
|
Sign up to set email alerts
|

Uso de plasma rico em plaquetas intra-articulares como tratamento pós-cirúrgico da ruptura do ligamento cruzado cranial num cão

Abstract: Uso de plasma rico em plaquetas intra-articulares como tratamento pós-cirúrgico

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…Similarly, on the basis of an analysis of synovial fluid, Yamada et al 14 concluded that treatment of joint lesions with PRP did not significantly minimize the degree of inflammation compared to saline solution. We agree with the authors that it is most likely that, despite the anti-inflammatory effects of PRP in some studies 15,27 , de-granulated platelets in tissue lesions may activate chemical mediators such as cytokines, and therefore, may alter the inflammatory response during tissue repair.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similarly, on the basis of an analysis of synovial fluid, Yamada et al 14 concluded that treatment of joint lesions with PRP did not significantly minimize the degree of inflammation compared to saline solution. We agree with the authors that it is most likely that, despite the anti-inflammatory effects of PRP in some studies 15,27 , de-granulated platelets in tissue lesions may activate chemical mediators such as cytokines, and therefore, may alter the inflammatory response during tissue repair.…”
Section: Discussionsupporting
confidence: 83%
“…The sample size used in this study was set because of bioethical issues and to ensure that the number of animals included would provide reliable and valid scientific results in terms of statistical significance. In addition, previous work performed and published by the researchers corroborates the use of smaller sample sizes, as planned in this study 1,8,12,14,15 .…”
Section: Methodssupporting
confidence: 84%
“…[64,65] It is therefore a way to track in vivo evolution of articular processes and their treatment. The limitations in second arthroscopic evaluation in clinical practice and the diversity of clinical situations [13,16,28,29] indicate the need for research that continuously assesses the process and treatment, as was performed in the first stage of this study. One of the difficulties encountered in this experimental model was the minimum quantity of synovial fluid in healthy joints, that is, 0.1 to 0.2 mL, which prevented the evaluation of the parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the lack of the standardization of the techniques employed, the literature reports promising clinical results in humans [22][23][24], horses [25][26][27], and dogs. [13,16,28,29] Clinical studies have shown early recovery and pain relief, as observed in the evaluation of dogs after receiving treatment for a rupture of the cranial cruciate ligament [13,29] and the fragmented coronoid process. [13,28,29] Because APC stimulates the healing of tissue, it has been used to treat different joint injuries, such as osteoarthritis, osteochondrosis, hip and elbow dysplasia, chondral defects, tendinitis, bursitis, menisci injuries, muscle injuries, wounds, and fractures, and it has been used as an adjunct in the treatment of the rupture of the cruciate ligament.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation